2018
DOI: 10.1155/2018/4630371
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Used for Treatment of Diarrhoeal Related Diseases in Ethiopia

Abstract: This paper presents a review of relevant antidiarrhoeal medicinal plants based on the fundamental knowledge accumulated by indigenous people of Ethiopia. The review includes an inventory carried out on the phytochemical and pharmacological analysis of plant species used in the treatments of diarrhoeal diseases. This study is based on a review of the literature published in scientific journals, books, theses, proceedings, and reports. A total of 132 medicinal plants used by local people of Ethiopia are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 71 publications
9
46
2
3
Order By: Relevance
“…Since an action on conservation and sustainable use of medicinal plants need involvement of various sectors and greater public support, it needs a continuous task of creating public awareness [ 45 ]. The review made by Megersa et al [ 46 ] suggested that identifying serious threats to medicinal plants and how local people manage medicinal plants will help to understand the best conservation strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Since an action on conservation and sustainable use of medicinal plants need involvement of various sectors and greater public support, it needs a continuous task of creating public awareness [ 45 ]. The review made by Megersa et al [ 46 ] suggested that identifying serious threats to medicinal plants and how local people manage medicinal plants will help to understand the best conservation strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the medicinal plants are Zehneria scabra (Linn. f.) (Cucurbitaceae) [7], Croton macrostachyus Hochst. ex Delile (Euphorbiaceae) [7][8][9], Lepidium sativum L. (Brassicaceae), Rumex nervosus Vahl.…”
Section: Introductionunclassified
“…f.) (Cucurbitaceae) [7], Croton macrostachyus Hochst. ex Delile (Euphorbiaceae) [7][8][9], Lepidium sativum L. (Brassicaceae), Rumex nervosus Vahl. (Polygonaceae), and Verbascum sinaiticum Benth (Scrophulariaceae) [7].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Most of the medicinal plant species were reported to be processed through crushing followed by pounding and chewing. Ethnobotanical studies conducted in different parts of the country (Ethiopia) [36,37,43,44] reported similar results.…”
Section: Discussionmentioning
confidence: 64%